METHOD OF STRUCTURAL SYNTHESIS OF MANAGEMENT SYSTEM OF MEANS OF WATER TRANSPORT - Будолак, С. Ю.; Ткаченко, В. В.; Гуменніков, Р. В.; Шевченко, А. П. (Science-based technologies, 2019)
The article presents the results of research on the ways of development of ship management systems. The analysis of operation shows that the most promising direction of co-development of these systems is their integration, integration and creation on the basis of such an association of "integrated bridging control systems by the ship". Also, the research of modern control systems suggests that the concept of their construction is based on the use of modernization of existing equipment in conjunction with new modern systems. Therefore, the task of multicriteria optimization of the structure of the control system according to known characteristics of existing subsystems of complexes is actual. The analysis of scientific and engineering approaches for the development and implementation of integrated bridging control systems has revealed a number of systemic deficiencies and remarks. Therefore, the scientific task is to improve existing and develop new models and methods for analyzing and synthesizing the ship management system based on a priori estimates of the technical efficiency of component subsystems. The analysis of the methods and approaches of compromising the solution in the solution of the multicriteria optimization problem, performed in the article, revealed a well-known method of successive concessions. This method most logically and effectively takes into account both the experience of the decision maker and the possibilities of analytical methods of one-criterion optimization. Also, in the article the features of the method of structural synthesis of the system of management of means of water transport improved by the authors, which unlike the existing ones, use the intellectualized approach of determining the assignment between efficiency and cost using parametric models of fuzzy expert conclusions based on neural networks. It is argued that the realization of the results obtained in the work allows to analyze the various variants of control systems, allows to carry out a comparative analysis and to determine the best value system according to the costeffectiveness criterion.